2020
DOI: 10.1161/circresaha.118.314522
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Mediated Activation of Endogenous Gene Expression in the Postnatal Heart

Abstract: Rationale: Genome editing by CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 is evolving rapidly. Recently, second-generation CRISPR/Cas9 activation systems based on nuclease inactive dead (d)Cas9 fused to transcriptional transactivation domains were developed for directing specific guide (g)RNAs to regulatory regions of any gene of interest, to enhance transcription. The application of dCas9 to activate cardiomyocyte transcription in targeted genomic loci in vivo has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Common efforts from E. Olson's and L. Zelarayán's Labs resulted in the establishment of a mouse model for cardiomyocyte-specific, CRISPR-mediated transcriptional modulation. The system is based on the constitutive expression of dCas9VPR combined with systemic administration of gRNA driving dCas9 to specific loci via AAV serotype 9, which showed robust, safe and specific single or multiplex activation of targeted genes (92). This model represents a rapid and powerful technical platform for gene activation in postnatal cardiomyocytes in preclinical proof-of-concepts.…”
Section: Crispr-mediated Control Of Transcription In Preclinical Modelsmentioning
confidence: 99%
“…Common efforts from E. Olson's and L. Zelarayán's Labs resulted in the establishment of a mouse model for cardiomyocyte-specific, CRISPR-mediated transcriptional modulation. The system is based on the constitutive expression of dCas9VPR combined with systemic administration of gRNA driving dCas9 to specific loci via AAV serotype 9, which showed robust, safe and specific single or multiplex activation of targeted genes (92). This model represents a rapid and powerful technical platform for gene activation in postnatal cardiomyocytes in preclinical proof-of-concepts.…”
Section: Crispr-mediated Control Of Transcription In Preclinical Modelsmentioning
confidence: 99%
“… Cardiomyopathy Cardiomyocytes Myh6 Demonstrated the role of Myh6 in heart function Mice Adeno-associated virus 102 2. Atherosclerosis Embryo Apolipoprotein E ( ApoE ) and low density lipoprotein receptor ( LDLR ) To study human cardiovascular disease by accessing the level of biochemical constituents Pigs Genome editing 107 Fibroblast and myoblast Mef2d and Klf15 loci Controlling transcription in cardiomyocytes of the postnatal heart Mice Genome editing 108 3. Cardiac dysfunction Lineage-negative bone marrow cells TET2 and Dnmt3a Role of targeted genes in cardiac dysfunction and renal fibrosis Mice Lentivirus 109 4.…”
Section: Emerging Therapeutic Applications Of Crispr Technologymentioning
confidence: 99%
“…The success of these efforts to engineer biologically active, shelf-stable, pro-angiogenic small molecules suggests that in vivo modulation of the pathways that govern natural regenerative pathways may be possible in the near future. For example, a recent study from Schoger et al (2020) demonstrated the feasibility of using CRISP/Cas9 gene editing in vivo to modify cardiomyocyte (CM) gene expression in a mouse model. Neonatal mice, piglets, and rats all exhibit the capacity for natural myocardial regeneration after myocardial infarction, which is an encouraging sign that these strategies may be translatable to humans pending further study ( Wang et al, 2020b ).…”
Section: Molecular and Cellular Bioengineeringmentioning
confidence: 99%